The evolution of modern states : Sweden, Japan, and the United States - Steinmo, Sven. (Cambridge : Cambridge University Press, 2010)
'The Evolution of Modern States: Sweden, Japan, and the United States examines the politics, history, and public policy of three countries in three different continents. Written from an evolutionary perspective, it shows how these countries' economic systems, social welfare policies, and political institutions have co-evolved over time to give these countries remarkably different abilities to adapt to the pressures they face in the twenty-first century. The book's wide-ranging historical analysis will be of interest to students of history, politics, and political economy'--Provided by publisher.
Machine generated contents note: 1. Introduction: evolutionary narratives; 2. Sweden: the evolution of a bumble-bee; 3. The Japanese hybrid; 4. The United States: strong nation - weak state; 5. And yet it moves.
Includes bibliographical references and index.
Keywords: State, The -- History; Comparative government; Sweden -- Politics and government; Japan -- Politics and government; United States -- Politics and government